7th International Symposium on Artichoke, Cardoon and their wild relatives - L.V. Krivenkov (Овощи России, 2009)
Artichoke is a very promising culture in the world due to a wide range of horticulturally valuable characteristics. Each 3 year the international symposiums take place around the world to join scientists, breeders, company managers, industrial experts. In this year, The «Bretagne Biotechnologie Vegetale» institute (France) was bidding to host the 7th symposium on artichoke under the aegis of International Society for Horticulture Science ISHS, and other institutions.